Emerging Emitters and Global Carbon Mitigation Efforts - Cui, Can (World Bank, Washington, DC, 2021)
International efforts to avoid dangerous climate change have historically focused on reducing energy-related carbon-di-oxide (CO2) emissions from countries with the largest economies, including the EU and U.S., and/or the largest populations, such as, China and India. However, in recent years, emissions have surged among a different, much less-examined group of countries, raising the issue of how to address a next generation of high-emitting economies that need strong growth to reduce relatively high levels of poverty. They are also among the countries most at risk from the adverse impacts of climate change. Compounding the paucity of analyses of these emerging emitters, the long-term effects of the Coronavirus (COVID-19) pandemic on economic activity and energy systems remain unclear. Here, the authors analyze the trends and drivers of emissions in each of the fifty-nine developing countries whose emissions over 2010-2018 grew faster than the global average (excluding China and India), and then project their emissions under a range of pandemic recovery scenarios. Although future emissions diverge considerably depending on responses to Coronavirus (COVID-19) and subsequent recovery pathways, the authors find that emissions from these countries nonetheless reach a range of 5.1-7.1 Gt CO2 by 2040 in all their scenarios, substantially in excess of emissions from these regions in published scenarios that limit global warming to 2 degrees Celsius . The authors results highlight the critical importance of ramping up mitigation efforts in countries that to this point have played a limited role in contributing the stock of atmospheric CO2 while also ensuring the sustained economic growth that will be necessary to eliminate extreme poverty and drive the extensive adaptation to climate change that will be required.